PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK UNTUK MENINGKATKAN PRESTASI DAN KREATIVITAS MAHASISWA PRODI PENDIDIKAN ADMINISTRASI PERKANTORAN STAMBUK 2022 UNIVERSITAS NEGERI MEDAN - Irma; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to develop a flipbook based e-module as a learning medium in an effort to enhance student achievement and creativity in the office administration education study program. The background of this study is the need for innovative, interactive, and technology oriented learning media, especially are developed as alternatives to less attractive and visually restricted convensional medoa as well as accessibility. The study employs the method of research and development (R&D) by adapting the development model, 4-D (Define, Design, Define, Develop). The research subject consists of a media expert, an expert. Materials, linguists, and Fourth semester students on correspondence courses. Data collection techniwues are done through expert validation, student responses, and pre-test and post-test tests. The data was analyzed using descriptive statistics and standarized tests and independent examinations test through version 26 SPSS programs. Validation byexperts indicates that the developed e-modules scored an average worthiness score of 84.6%, which is included in the “ totally feasible ” category. The student response to the e-module shows a total value of 44.12 out of 50, which shows a very positive response. Preliminary results show an increase in average value from pre-test to post-test by 25.67 points with significant value 0.000 (p <0.05), which means that the increase is statistically significant. Meanwhile, independent test-tests indicate that there is a significant difference between experiment and control groups in terms of achievement (p=0.0044) as well as creativity (p=00039), it may be concluded that the flipbook based e-modules developed in this research are perfectly feasible, well received by students, and effective in promoting student achievement and creativity in the learning process. The emodules can be an innovative digital learning